Alu element in the RNA binding motif protein, X-linked 2 (RBMX2) gene found to be linked to bipolar disorder. - Pia Laine; William J Rowell; Lars Paulin; Steve Kujawa; Denise Raterman; George Mayhew; Jennifer Wendt; Daniel L Burgess; Timo Partonen; Tiina Paunio; Petri Auvinen; Jenny M Ekholm (PLoS ONE, 2021)
Objective We have used long-read single molecule, real-time (SMRT) sequencing to fully characterize a ~12Mb genomic region on chromosome Xq24-q27, significantly linked to bipolar disorder (BD) in an extended family from a genetic sub-isolate. This family segregates BD in at least four generations with 24 affected individuals. Methods We selected 16 family members for targeted sequencing. The selected individuals either carried the disease haplotype, were non-carriers of the disease haplotype, or served as married-in controls. We designed hybrid capture probes enriching for 5-9Kb fragments spanning the entire 12Mb region that were then sequenced to screen for candidate structural variants (SVs) that could explain the increased risk for BD in this extended family. Results Altogether, 201 variants were detected in the critically linked region. Although most of these represented common variants, three variants emerged that showed near-perfect segregation among all BD type I affected individuals. Two of the SVs were identified in or near genes belonging to the RNA Binding Motif Protein, X-Linked (RBMX) gene family-a 330bp Alu (subfamily AluYa5) deletion in intron 3 of the RBMX2 gene and an intergenic 27bp tandem repeat deletion between the RBMX and G protein-coupled receptor 101 (GPR101) genes. The third SV was a 50bp tandem repeat insertion in intron 1 of the Coagulation Factor IX (F9) gene. Conclusions Among the three genetically linked SVs, additional evidence supported the Alu element deletion in RBMX2 as the leading candidate for contributing directly to the disease development of BD type I in this extended family.